2004
DOI: 10.1074/jbc.m402035200
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide in Lipid Particles Enhances Heparan Sulfate Proteoglycan and Low Density Lipoprotein Receptor-related Protein-mediated Uptake by Macrophages

Abstract: Arterial wall sphingomyelinase (SMase) has been proposed to be involved in atherogenesis. SMase modification of lipoproteins has been shown to occur in atherosclerotic lesions and to facilitate their uptake by macrophages and foam cell formation. To investigate the mechanism of macrophage uptake enhanced by SMase, we prepared lipid emulsions containing sphingomyelin (SM) or ceramide (CER) as model particles of lipoproteins. SMase remarkably increased the uptake of SM-containing emulsions by J774 macrophages wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 76 publications
(65 reference statements)
4
53
0
1
Order By: Relevance
“…61,74,284) I have shown that SMase promotes the aggregation and fusion of lipid emulsions depending on ceramide formation. 287,288) I have also confirmed the existence of ceramide-enriched domains in emulsion particles by confocal fluorescence microscopy 288) (Fig. 4).…”
Section: Remnantssupporting
confidence: 51%
See 2 more Smart Citations
“…61,74,284) I have shown that SMase promotes the aggregation and fusion of lipid emulsions depending on ceramide formation. 287,288) I have also confirmed the existence of ceramide-enriched domains in emulsion particles by confocal fluorescence microscopy 288) (Fig. 4).…”
Section: Remnantssupporting
confidence: 51%
“…287) Ceramide formed in the particles by SMase enhances their uptake into J774 macrophages, although the increase in size or particle aggregation decreases their uptake. HSPGs and LRP are crucial for the ceramide-enhanced emulsion uptake, because heparin or lactoferrin inhibit the emulsion uptake.…”
Section: Remnantsmentioning
confidence: 99%
See 1 more Smart Citation
“…11) Elevated ceramide levels were recently shown to correlate with atherogenetic processes such as low-density lipoprotein (LDL) aggregation, 12) and form cell migration. 13) In relation to atherogenesis, we previously reported that the ceramide level in human plasma was positively correlated with both total cholesterol and oxidized apolipoprotein B-100 (oxLDL) levels. 14) Deevska et al 15) reported that LDL-SM content and sSMase activity in LDL receptor knockout mice, which were fed an atherogenic diet, were increased.…”
mentioning
confidence: 99%
“…Очевидно, что направленность реализуемых процессов определяется типом эффектора в составе комплекса, а также тем, какой именно представитель семейства МГ является доминирующим в общем пуле комплексов. Необходимо также отметить, что система представляет собой саморегулирующийся механизм, поскольку известно, что экспрессия ЛРП регулируется транспортируемыми МГ субстанциями -интерлейкином-10, интерфероном-g, и лактоферином [13,14]. We have conducted a series of experiments, for specification of mechanisms which proteins of the macroglobulin family deliver regulatory substances inside of a cells.…”
Section: рисунокunclassified